2022
DOI: 10.1016/j.lanwpc.2021.100361
|View full text |Cite
|
Sign up to set email alerts
|

Etiological and epidemiological features of acute meningitis or encephalitis in China: a nationwide active surveillance study

Abstract: Background Acute meningitis or encephalitis (AME) results from a neurological infection causing high case fatality and severe sequelae. AME lacked comprehensive surveillance in China.Methods Nation-wide surveillance of all-age patients with AME syndromes was conducted in 144 sentinel hospitals of 29 provinces in China. Eleven AME-causative viral and bacterial pathogens were tested with multiple diagnostic methods.Findings Between 2009 and 2018, 20,454 AME patients were recruited for tests. Based on 9,079 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…On joinpoint analysis, the authors found an increasing turnpoint at 25 years of age for JEV, hence, they advocated for a booster vaccine for this at the age of 25. 6 Similarly, a previous study showed the benefit of meningitis B vaccinations in preventing Neisseria meningitidis infections, demonstrating the key role of vaccinations in meningitis infection prevention. 7 …”
mentioning
confidence: 81%
See 4 more Smart Citations
“…On joinpoint analysis, the authors found an increasing turnpoint at 25 years of age for JEV, hence, they advocated for a booster vaccine for this at the age of 25. 6 Similarly, a previous study showed the benefit of meningitis B vaccinations in preventing Neisseria meningitidis infections, demonstrating the key role of vaccinations in meningitis infection prevention. 7 …”
mentioning
confidence: 81%
“…In The Lancet Regional Health – Western Pacific , Wang and colleagues report the results of a nationwide surveillance study across China, looking for viral and bacterial pathogens in patients with acute meningitis or encephalitis. 6 This large study, spanning a decade, is an important contribution towards understanding the etiology and epidemiology of meningitis and encephalitis.…”
mentioning
confidence: 99%
See 3 more Smart Citations